Cryptic variation in RNA-directed DNA-methylation controls lateral root development when auxin signalling is perturbed - Zaigham Shahzad (Nature Portfolio, 2020)
Developmental plasticity of plant root systems has been intensively studied, but the mechanisms underpinning robustness remain unclear. Here, the authors show that DNA-methylation-mediated transcriptional repression serves as a backup system to control lateral root development when auxin signalling is perturbed.